Produção e caracterização de células solares fotossensibilizadas por corante baseadas em filmes finos de titanatos e óxidos metálicos nanoestruturados - Souza, Antonio Paulo Santos (2019)
Nanoparticles of TiO 2 have been the main semiconductor applied in dye-sensitized solar cells. However, with the progress made in the nanotechnology field, new semiconductors with varied morphologic characteristics are been broadly investigated. In this thesis work titanate nanotubes (NaTiNT) and nanoribbons, were obtained by the hydrothermal method from TiO 2 anatase. These materials were deposited on conductive substrate by electrophoresis, with and without thermal treatment, sensitized by ruthenium-based dye and used as work electrode. Exposing those photovoltaic devices to visible radiation, with films before thermal treatment, a short-circuit current density (J SC ) of 0.0012 mA/cm 2 was observed for the cell with NaTiNT, a current density of 0.0398 mA/cm 2 for the cell with Nanoribbons, and a current density of 0.4028 mA/cm 2 for the cell with TiO 2 as electrode. After thermal treatment, a short-circuit current density of 0.4269 mA/cm 2 was observed for the cell with NaTiNT, a current density of 0.0765 mA/cm 2 for the Nanoribbons cell, and, finally, a current density of 0.3310 mA/cm 2 for the cell with TiO 2 as electrode. Moreover, thin films of tin oxide were synthesized by technique of electrophoresis and applied as working electrodes in dye sensitized solar cells (DSSCs). In this stage, five samples of films were obtained by different time of deposition, heat treated and characterized by structural and optical techniques while the cells were tested by current vs. voltage, electrochemical impedance and quantum eficiency measurements. The highest efficiency obtained was 3.89% using a SnO 2 thin film without any chemical post-treatment. The new morphological, structural and optical characteristics of these nanoparticles may contribute for the development and research of new generation photovoltaic devices.